Provision of disable facilities in higher education building / Mohd Syafiq Aizuddin Darus - Darus, Mohd Syafiq Aizuddin (2020)
ln era of modernization, disable facilities management in higher education play a significant role to achieve the needs and accommodations in the best quality for disabled people. There are consist of eight elements such as classroom, ramp, service counter, ramp, staircase, pathways, toilet and parking. The standard requirement of the disabled facilities according the laws must be followed by the organization. The disabled people must be treated equally with the ordinary people and the right to access facilities or used the accommodations that been provide. The aim of this research is to assess the level of student's awareness towards disable facilities that implemented in Universiti Teknologi NIARA Sarawak. There are three objectives outlined in achieving the aim of the research, firstly to identify the element of disabled facilities at higher education, secondly, to investigate the level of student's awareness on disabled facilities and lastly, to evaluate the elements that highly influences the student's awareness towards disable facilities. The methodology was adopted for the research is using quantitative method which is questionnaire survey and the data was analyzed by using SPSS software. The respondents are students from campus Kota Samarahan 1 and campus Kota Samarahan 2. The result throughout this finding mostly student's awareness towards disable facilities in Universiti Teknologi TVARA Sarawak are moderate. Hence, the recommendation was made to improve the facilities especially for disable people.